Development of Android-Base Learning Media to Determine Digital Literacy at Public Vocational High School - Ayu Arti Putri Handayani; Siti Mujdalipah; Yatti Sugiarti (Journal of Research and Innovation In Open and Distance Learning, 2022)
The development of information and communication technology (ICT) in the era of globalization has had a major influence in all aspects of life, including in the world of education. In the development of information and communication technology, Android-based learning media was developed as a means of learning for students. The limited number of books that can be used by students and in conditions like now where the learning process is carried out online requires learning media that can be used and accessed easily by students. The objectives of this study are: (1) developing android-based learning media, (2) understanding the feasibility of android-based learning media, and (3) evaluating the digital literacy of students by using android-based learning media as a learning resource. The development of this android-based learning media uses a research and development model with stages including identification of potential and problems, data collection, product design, design validation, design revision, small-scale trials, product revisions, large-scale trials, and product revision. The results of this study indicate that the learning media developed was found "Decent" by material experts, media experts and linguists and students stated "Very Decent" to be used as learning media in the subject of Plantation and Herbal Commodity Processing Production. Furthermore, the learning media is applied in learning by using One Shot Case Study. Based on the results obtained, the digital literacy that students have is already in the "Very High" category for the aspect of using. As for the understanding aspect, the indicators of analyzing and creating are in the â€œHighâ€ category and the indicators for reflecting and acting are in the â€œVery Highâ€ category